INFLUENCE OF MONETARY POLICY ON THE FINANCIAL PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA - Udeh , Amara Nkechi; Eze, Ifeanyi Chukwuemeka (Ayden International Journal of Applied Economics, Finance and Accounting, 2024)
This study examined empirically the impact of monetary policy on the performance of Nigeria deposit money banks between 1981 -2021. The data for study were extracted from Central Bank of Nigeria statistical bulletin 2021. The study employed various econometric tools to analyse the data obtained, but specifically applied the Generalized Method of Moments due to dynamic nature of the study. Deposit money banks performance as the dependent variable was proxied by total asset of banks while monetary policy variables were proxied by monetary policy rate, loan to deposit ratio and liquidity ratio respectively. The result showed that monetary policy rate and loan to deposit significantly impact total asset. This result is in line with the quantity theory of money supply. We therefore recommend that monetary policy rate should be optimized appropriately to boost the flow of money and economic performance in the country.